Revealing the Influence of Microparticles on Geopolymers’ Synthesis and Porosity - Dumitru Doru Burduhos Nergis (Materials, 2020)
Geopolymers are zeolites like structures based on hydrated aluminosilicates units of SiO4 and AlO4. These units, known as poly(sialate), poly(sialate)-siloxo or poly(sialate)-disiloxo are chemically balanced by the group I cations of K+, Li+, or Na+. Simultaneously, the chemical reaction of formation, known as geopolymerization, governs the orientation of the unit, generating mesoporous structures. Multiple methods can be used for pore structure and porosity characterization. Among them, nuclear magnetic resonance (NMR) relaxometry allows the detection of the porous structure in a completely nonperturbative manner. NMR relaxometry may be used to monitor the relaxation of protons belonging to the liquid molecules confined inside the porous structure and, thus, to get access to the pore size distribution. This monitoring can take place even during the polymerization process. The present study implements transverse relaxation measurements to monitor the influence introduced by the curing time on the residual liquid phase of geopolymers prepared with two different types of reinforcing particles. According to our results, the obtained geopolymers contain three types of pores formed by the arrangement of the OH− and Si groups (Si-OH), Si-O-Si groups, Si-O-Al groups, and Si-O rings. After 48 days, the samples cured for 8 h show a high percentage of all three types of pores, however, by increasing the curing time and the percentage of reinforcing particle, the percent of pores decrease, especially, the gel pores.